On the Structure and History of Russian. Selected Essays With a Preface by Henrik Birnbaum - Worth, Dean S. (Slavistische Beitraege, 1977)
The essays comprised in this volume fall naturally into two groups, one treating synchronic facets of Russian (and some further Slavic) linguistic structure, the other elucidating diachronic aspects of Russian - or, more generally, East Slavic - linguistic evolution.